Financial performance, firm value, transparency and corporate governance. Evidences from family-owned business in UAE. Issue 3 (3rd July 2022) - Sadiq, Misbah; Gebba, Tarek Roshdy Abdelhalem
Abstract: The purpose of this study is to investigate the relationship among financial performance (FP), firm value (FV), transparency and corporate governance (CG) from family-owned business in the United Arab Emirates (UAE). This study used secondary data sets for analysis. This study applied descriptive statistics and cross-section analysis in order to better understand the actual facts and figures. The results indicate that majority of analysed companies do not provide a public access to their annual reports. However, comparison of average revenues for companies from each group allowed that there is a statistically significant difference found in revenue received by private family firms and public family firms. The public family companies receive 1.5 times higher annual revenue as compare to private family-owned companies. Finally, the linear regression model shows that there is insignificant relationship exist between corporate governance and company's financial performance.